The influence between gestational age and postural control, a systematic review - Tuñón-Domínguez, Isabel; Cuesta-Gómez, Alicia; Molina-Rueda, Francisco; Juárez-Vela, Raúl; Ruiz de Viñaspre-Hernández, Regina; Santolalla-Arnedo, Iván; Sánchez-González, Juan Luis; Carratalá-Tejada, María (Frontiers in Pediatrics, 2022)
The central nervous system (CNS) of preterm infants might have some peculiarities which distinguish it from that of full term infants. The difficulties associated with prematurity are the main cause of deaths all over the world during the new-born period after community-acquired pneumonia, and the second cause of deaths worldwide in children under five years old. Early recognition of signs indicating fragile postural control in premature infants can support understanding and help prevent and early intervention on possible future neuromotor dysfunctions in these subjects. The purpose of this paper is to determine if there is a qualitatively different development of postural control in premature infants without neurological involvement and infants born at term. We conducted a systematic review of longitudinal and cross-sectional case-control studies published between 2010 and March 2020 on this topic. The evaluation of parameters related to postural control was also included. The methodological quality of the selected works was evaluated using the CASPe critical reading programme for cases and controls. PRISMA guidelines for systematic reviews were followed for prematurity and postural control. 16 articles were included. The total sample amounted to 3460 participants, of which 1860 in the preterm group, and 1600 in the control group. All the studies found show a poorer postural control by the group of children born preterm compared to the group of children born at term and one study indicating more limited postural control with higher prematurity. Regarding the methodological quality according to CASPe, those studies exceeding half of the total score were considered of adequate quality.